Self-Reported Mobile Health-Based Risk Factor and CHA2DS2-VASc-Score Assessment in Patients With Atrial Fibrillation: TeleCheck-AF Results - Hermans, Astrid N. L.; Gawałko, Monika; Hillmann, Henrike A. K.; Sohaib, Afzal; van der Velden, Rachel M. J.; Betz, Konstanze; Verhaert, Dominique; Scherr, Daniel; Meier, Julia; Sultan, Arian; Steven, Daniel; Terentieva, Elena; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction. The TeleCheck-AF approach is an on-demand mobile health (mHealth) infrastructure incorporating mobile app-based heart rate and rhythm monitoring through teleconsultation. We evaluated feasibility and accuracy of self-reported mHealth-based AF risk factors and CHA₂DS₂-VASc-score in atrial fibrillation (AF) patients managed within this approach. Materials and Methods. Consecutive patients from eight international TeleCheck-AF centers were asked to complete an app-based 10-item questionnaire related to risk factors, associated conditions and CHA2DS2-VASc-score components. Patient’s medical history was retrieved from electronic health records (EHR). Results. Among 994 patients, 954 (96%) patients (38% female, median age 65 years) completed the questionnaire and were included in this analysis. The accuracy of self-reported assessment was highest for pacemaker and anticoagulation treatment and lowest for heart failure and arrhythmias. Patients who knew that AF increases the stroke risk, more often had a 100% or ≥80% correlation between EHR- and app-based results compared to those who did not know (27% vs 14% or 84% vs 77%, P=0.001). Thromboembolic events were more often reported in app (vs EHR) in all countries, whereas higher self-reported hypertension and anticoagulant treatment were observed in Germany and heart failure in the Netherlands. If the app-based questionnaire alone was used for clinical decision-making on anticoagulation initiation, 26% of patients would have been undertreated and 6.1% - overtreated. Conclusion. Self-reported mHealth-based assessment of AF risk factors is feasible. It shows high accuracy of pacemaker and anticoagulation treatment, nevertheless, displays limited accuracy for some of the CHA2DS2-VASc-score components. Direct health care professional assessment of risk factors remains indispensable to ensure high quality clinical-decision making.